2007
DOI: 10.1242/jcs.03315
|View full text |Cite
|
Sign up to set email alerts
|

Sorting of Fas ligand to secretory lysosomes is regulated by mono-ubiquitylation and phosphorylation

Abstract: Fas ligand (FasL), a potent mediator of apoptosis expressed by CTL and NK cells, is sorted into the inner vesicles of secretory lysosomes for release via exosome-like vesicles. Previous studies identified a proline-rich domain in the cytoplasmic tail required for sorting FasL to secretory lysosomes, but the mechanisms by which this occurs have not been identified. Here we demonstrate that the PRD of FasL binds Fgr, Fyn and Lyn tyrosine kinases, leading to phosphorylation of FasL. Loss of phosphorylation reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
83
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(90 citation statements)
references
References 31 publications
7
83
0
Order By: Relevance
“…Mechanisms that control TRAIL translocation from the intracellular pools to the cell surface [51] are currently unknown and are the subject of continuing investigation. Monoubiquitination was shown to play an important role in the protein translocation of Fas Ligand [52]. However, protein modifications of TRAIL linked with its intracellular trafficking are still incompletely investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanisms that control TRAIL translocation from the intracellular pools to the cell surface [51] are currently unknown and are the subject of continuing investigation. Monoubiquitination was shown to play an important role in the protein translocation of Fas Ligand [52]. However, protein modifications of TRAIL linked with its intracellular trafficking are still incompletely investigated.…”
Section: Discussionmentioning
confidence: 99%
“…These include the Src-like kinases Fyn, Lyn, and Fgr and the adaptor proteins Nck, Grb2 and PSTPIP. 28,[35][36][37][38][39] Of interest is the recently described interaction between Nck and FasL, as Nck likely links preformed and granule-stored FasL to WASP and the cytoskeleton. 38 In agreement with our observation that PMA-induced FasL degranulation was latrunculin B-sensitive it was found that the delivery of FasL to the immunological synapse was dependent on actin filament formation.…”
Section: Discussionmentioning
confidence: 99%
“…In the second, FasL is anchored to intracellular membrane microvesicles, where it is stored until expressed on the cell surface in response to physiological stimuli. The last corresponds to a soluble FasL, which is generated by degradation of the membranous shape (during the first minutes of expression) due to the activity of a metalloprotease matrix whose function is to catalyze the degradation of extracellular matrix proteins (108)(109)(110)(111). The soluble FasL molecule has either pro-apoptotic or antiapoptotic properties since soluble FasL is an inefficient homotrimer binding to Fas.…”
Section: Fas-fasl Intercellular Linkage-mediated Pathwaymentioning
confidence: 99%